A quarter of a century of experience in redox biochemistry: revealing the role of oxidative stress in health and disease - Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
Oxidative stress is a pathophysiological phenomenon that occurs during various physiological processes, as a consequence of aging, but also in many diseases. Oxidative stress "eruption" occurs when its factors - free radicals are increased in pathological conditions, when their creation overcomes the mechanisms of antioxidant protection. Measurement of redox status parameters gives new biomarkers of various diseases. During more than 25 years of dealing with this topic, we analyzed the redox status of a large number of patients with various diseases: cardiovascular, stroke, kidney disease, diabetes, cancer, obesity. Redox status was determined in a large number of healthy subjects, and in special physiological conditions: pregnancy, athletes, children, elderly, in subjects after antioxidants’ supplementation. Oxidative stress markers measurement is applied in pharmacological studies on several different animal models: atherosclerosis, multiple sclerosis, blast injuries, poisoning, rheumatoid arthritis. These types of studies provide insight into cellular oxidative stress development, mechanisms involved in the disease development, insight into the possibility of its modulation under the therapy influence. Many years of experience in the oxidative stress analysis, enabled us to develop a system for testing the antioxidant potential of biologically active compounds in the serum pool of healthy individuals. The redox status of the respondents is "chemical ID card", which changes in various diseases. "Redox imbalance" diagnosis would allow determining the type of antioxidants’ application, dosing regimen, monitoring the therapy effects, which is the application of the principles of precision (personalized) medicine, as the ideal of modern therapy.